Sarcopenia is associated with the Geriatric Nutritional Risk Index in elderly patients with poorly controlled type 2 diabetes mellitus. Issue 8 (24th March 2022) - Matsuura, Shun; Shibazaki, Koji; Uchida, Reiko; Imai, Yukiko; Mukoyama, Takuya; Shibata, Shoko; Morita, Hiroshi
ABSTRACT: Aims/Introduction: Diabetes and sarcopenia have a two‐way relationship with each other with advanced age. Additionally, malnutrition is correlated with a higher risk of sarcopenia in elderly patients. This study evaluated the association between sarcopenia and geriatric nutritional risk index (GNRI) in elderly patients with type 2 diabetes mellitus. Materials and Methods: Patients with type 2 diabetes mellitus aged ≥60 years were recruited from June 2018 to August 2020. This study analyzed 234 patients, who completed a physical performance test required for the diagnosis of sarcopenia. To investigate the effect of GNRI on sarcopenia, logistic regression analyses was used. Results: Patients with sarcopenia were significantly older with a lower body mass index (BMI) and GNRI compared with normal patients. The GNRI showed a positive correlation with the skeletal muscle index (SMI) and handgrip strength (SMI: R = 0.486, P < 0.001 for male; R = 0.589, P < 0.001 for female, handgrip strength: R = 0.470, P < 0.001 for male, R = 0.364, P < 0.001 for female). In the multivariate logistic regression model, a higher GNRI was associated with a lower risk of sarcopenia in older men and women with diabetes (adjusted odds ratio [OR], 0.892; 95% confidence interval [CI], 0.839–0.948 for male; adjusted OR, 0.928; 95% CI, 0.876–0.982 for female). One year of diabetes treatment improved the GNRI in the sarcopenia group with type 2 diabetes mellitus. Conclusions: A low GNRI was associated with an increased risk of sarcopenia in elderly patients with type 2 diabetes mellitus. Treatment with glucose‐lowering drugs improved the GNRI in the sarcopenia group. Abstract : Low GNRI levels were associated with an increased risk of sarcopenia in elderly patients with type 2 diabetes mellitus. Treatment with glucose‐lowering drugs improved the GNRI in the male sarcopenia group.